Evidence of a modest price decline in US broadband services - Shane Greenstein; Ryan McDevitt (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2010)
In this paper, we construct a price index for broadband services in the United States between 2004 and 2009. We analyze over 1500 service contracts offered by DSL and cable providers in the United States. We employ a mix of matched-model methods and hedonic price index estimations to adjust for qualitative improvements. In general, we find some evidence of a quality-adjusted price decline, but the evidence points towards a modest decline at most. Our estimates of the price decline range from 3% to 10% in quality-adjusted terms for the five-year period, which is faster than BLS estimates for the last three years. These modest price declines look nothing like other parts of electronics, such as computers or integrated circuits, which raises many questions. The results also inform a range of policy discussions concerning US broadband services.
Keywords: 330; Breitbandkommunikation; Dienstleistungsqualität; Preis; Hedonischer Preisindex; USA